Negative electrode material, preparation method thereof and lithium ion battery
By forming a cladding layer on the surface of natural graphite and increasing Young's modulus, the problem of poor expansion and circulation performance of natural graphite in lithium-ion batteries is solved, and the characteristics of low expansion and long circulation are achieved, which improves the overall performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411967159.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
When natural graphite is the negative electrode material of lithium-ion batteries, it has large volume deformation (expansion) and cannot be recovered, resulting in limited circulation performance.
By forming a cladding layer on the surface of natural graphite and adjusting the heat treatment process, the Young's modulus of the negative electrode material can be improved, so that it can better maintain the microcrystal structure during the lithium ion deintercalation process and reduce irreversible deformation.
The low expansion and long circulation performance of the negative electrode material are achieved, and the cycle stability and fast charging performance of lithium-ion batteries are improved.
Smart Images

Figure CN119764405A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion batteries, and in particular to a negative electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] With the development of lithium-ion batteries, high-capacity batteries have become a hot topic in current research. Natural graphite has the advantages of high capacity and high compactness, and it does not require graphitization, which can greatly reduce energy consumption and carbon dioxide emissions, making it very suitable for use as a negative electrode for lithium-ion batteries in the context of carbon neutrality. However, natural graphite itself is relatively soft, so during the process of lithium ion insertion and extraction, it will undergo a large volume deformation that cannot be recovered, that is, irreversible deformation occurs. This characteristic poses a great challenge to the cycle performance of lithium-ion batteries. Summary of the invention
[0003] In view of the above problems existing in the prior art, the present invention provides a negative electrode material and a preparation method thereof and a lithium ion battery to improve the expansion problem of natural graphite.
[0004] To achieve the above-mentioned object and other related objects, the first aspect of the present invention provides a negative electrode material, wherein the Young's modulus E of the negative electrode material is: 8GPa≤E≤17Gpa, and the negative electrode material comprises natural graphite and a coating layer coated on the surface of the natural graphite.
[0005] In one embodiment of the present invention, the value of the powder compaction P of the negative electrode material at 80 MPa is 1.66≤P≤1.74 g / cm 3 .
[0006] In one embodiment of the present invention, after the negative electrode material is cold pressed at 160 MPa for 10 seconds, the micropore volume V of the pores with a pore size of 0.2 to 2 nm is 0.2-2 =14≤V 0.2-2 ≤20cm 3 / Kg.
[0007] In one embodiment of the present invention, the coating layer includes amorphous carbon, and the mass of the amorphous carbon accounts for 2.5% to 6% of the mass of the natural graphite.
[0008] In one embodiment of the present invention, the particle size Dv50 of the negative electrode material is 5 μm to 20 μm.
[0009] Another aspect of the present invention provides a method for preparing a negative electrode material, the preparation method comprising the following steps:
[0010] The natural flake graphite raw material is crushed and shaped to obtain a graphite precursor;
[0011] Performing a thermal shaping treatment on the graphite precursor, and then performing a cold quenching treatment on the graphite precursor by a gradient cooling method to obtain a spherical precursor;
[0012] The spheroidized precursor is vacuum calcined, and then a coating layer is formed on the surface of the spheroidized precursor to obtain a negative electrode material.
[0013] In one embodiment of the present invention, the step of subjecting the graphite precursor to thermal shaping treatment and then subjecting the graphite precursor to cold quenching treatment by a gradient cooling method comprises:
[0014] The graphite precursor is transferred into a jet mill and heated to a first temperature, and subjected to ultra-high frequency heat shaping at 100 Hz to 140 Hz for 0.5 h to 2 h;
[0015] Afterwards, a first inert gas is introduced into the jet mill to cool the temperature to a second temperature, and ventilation is maintained at the second temperature for 1 hour to 3 hours while shaping;
[0016] Then, a second inert gas is introduced into the jet mill to cool the temperature to a third temperature, and the gas is maintained for 1 to 3 hours while shaping the product to obtain a spherical precursor;
[0017] Among them, the first temperature is 600℃ to 800℃; the temperature difference between the first temperature and the second temperature is 100℃ to 400℃, the temperature difference between the second temperature and the third temperature is 100℃ to 400℃, the flow rate L1 of the first inert gas is 5L / min to 10L / min; the flow rate L2 of the second inert gas is 30L / min to 60L / min.
[0018] In one embodiment of the present invention, the temperature of the vacuum calcination is 450°C to 550°C; the step of forming a coating layer on the surface of the spherical precursor comprises: transferring the vacuum calcined precursor to a solution containing a carbon-containing precursor, stirring, filtering and drying, and collecting the powder; then calcining the powder at 750°C to 1100°C under an inert atmosphere for 4 to 8 hours to obtain a negative electrode material; and / or the particle size Dv50 of the graphite precursor is 30μm to 50μm, and the particle size distribution width (Dv90-Dv10) / Dv50 is less than 1.1.
[0019] In one embodiment of the present invention, the carbon-containing precursor includes one or more of C9 petroleum resin, phenolic resin, and asphalt.
[0020] The present invention also provides a lithium ion battery, the lithium ion battery comprises a negative electrode plate, the negative electrode plate comprises any of the negative electrode materials described above or a negative electrode material prepared by any of the preparation methods described above.
[0021] The negative electrode material of the present invention has a high Young's modulus, so that the negative electrode material particles have a high mechanical strength, and can better maintain the microscopic crystal structure when lithium ions are deintercalated, and a small irreversible deformation occurs, thereby having better cycle performance. In addition, the negative electrode material has a high Young's modulus, so that the powder compaction of the material is maintained within an appropriate range, while having a high energy density, ensuring a high porosity at the pole sheet level, and having excellent fast charging performance; and the negative electrode material can maintain a large amount of micropore volume under high pressure, so that it has more rapid lithium insertion channels, ensuring that the material has good fast charging performance under high energy density.
[0022] When preparing the negative electrode material, the present invention uses natural flake graphite as a raw material, adjusts the heat treatment process, and uses a gradient cooling method to cold-quench the precursor, so that the material has a higher Young's modulus while maintaining the kinetic performance advantages of natural graphite, thereby achieving the characteristics of low expansion and long cycle. The preparation method of the present invention can effectively improve the expansion performance of natural graphite, and is simple and easy to operate, greatly reducing the cost and energy consumption of the negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.
[0024] Figure 1 FIG. 1 is a flow chart of a method for preparing a negative electrode material according to an embodiment of the present invention. DETAILED DESCRIPTION
[0025] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied by other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and the features in the embodiments can be combined with each other without conflict. The test methods for which specific conditions are not specified in the following embodiments are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0027] In this article, when it comes to numerical ranges, unless otherwise specified, the distribution of optional values within the numerical range is considered continuous and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical range, as well as every value between the two numerical endpoints. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined.
[0028] In this article, the test of Young's modulus refers to GB / T 34186-2017; the test of powder compaction refers to GBT 24533-2009; the test of micropore volume refers to GB / T 19587-2017.
[0029] Natural graphite has the advantages of high capacity and high compactness, but the material of natural graphite itself is relatively soft, and it will undergo large volume deformation during the insertion and extraction of lithium ions (it cannot go back after expansion, that is, irreversible deformation), which poses a great challenge to the cycle performance of lithium-ion batteries. In the prior art, there is a method of improving the expansion performance of natural graphite by graphitizing it. Although this method can improve the expansion performance of natural graphite, it will also greatly increase the cost and energy consumption, and will deteriorate the low-temperature performance of natural graphite.
[0030] Based on this, the present invention provides a negative electrode material, a method for preparing the negative electrode material, and a lithium ion battery comprising the negative electrode material. By controlling the Young's modulus of the negative electrode material, the particles have a certain hardness, and the microscopic crystal structure can be better maintained when lithium ions are inserted and removed, resulting in smaller irreversible deformation, thereby having better cycle performance.
[0031] The first aspect of the present invention provides a negative electrode material, which includes natural graphite and a coating layer coated on the surface of the natural graphite, and the Young's modulus E of the negative electrode material is 8GPa≤E≤17Gpa. Young's modulus indicates the degree of change in the initial length per unit cross section of the powder after being subjected to a certain tensile stress, which reflects the deformation of the material under stress. The calculation formula of Young's modulus is E=σ / ε, where σ represents the stress per unit area of the material, and ε represents the strain per unit length. It can be seen from the calculation formula of Young's modulus that when the stress σ per unit area of the material remains unchanged, the larger the Young's modulus E, the smaller the strain ε per unit length, indicating that the material is less likely to deform, that is, the greater the hardness; conversely, the smaller the Young's modulus E, the larger the strain ε per unit length, indicating that the material is more easily deformed, that is, the smaller the hardness. The negative electrode material will undergo lithium ion embedding and extraction during the charge and discharge process of the lithium ion battery. If the hardness of the negative electrode material is small (the material is soft), a large volume deformation will occur during the lithium ion embedding and extraction process, and it will not recover, that is, irreversible deformation will occur, which is not conducive to the cycle of the lithium ion battery; while the negative electrode material has a large hardness, it can better maintain the microscopic crystal structure during the lithium ion extraction process, and a small irreversible deformation will occur, so that the lithium ion battery has better cycle performance; but the hardness of the negative electrode material is too large, and it is not easy to compact, resulting in a low compaction density of the negative electrode, thereby affecting the energy density of the battery. Therefore, the Young's modulus of the negative electrode material can maintain good mechanical strength within a suitable range without affecting the compaction of the negative electrode, thereby having better cycle performance. The Young's modulus E of conventional natural graphite is below 5GPa, the texture is soft, and the cycle performance is poor; the Young's modulus E of the negative electrode material of the present invention is within 8GPa≤E≤17Gpa, which can have the characteristics of low expansion and long cycle while maintaining the dynamics of natural graphite. In some embodiments, the Young's modulus E of the negative electrode material may be 8 GPa, 10 GPa, 13 GPa, or 17 GPa, etc.
[0032] In one embodiment, the value of the powder compaction P of the negative electrode material at 80 MPa is 1.66≤P≤1.74 g / cm 3. Powder compaction indicates the total mass of the powder sample per unit volume, and refers to the process in which the particles of the powder material are rearranged under the action of external pressure, the gaps are reduced, and the density is increased. Therefore, under different external pressures, the negative electrode material presents different compaction values. The powder compaction of the negative electrode material of the present invention uses 80MPa as the test pressure, which corresponds to the preparation conditions of the battery negative electrode. Powder compaction is closely related to the compaction density of the negative electrode pole piece. The greater the powder compaction, the greater the compaction density of the negative electrode pole piece, and the compaction density of the pole piece affects the performance of the battery. If the powder compaction of the negative electrode material is too high, the compaction density of the pole piece will be too high, the gap between the particles will become smaller, the wettability of the pole piece will become worse and worse, and the insertion / extraction behavior of lithium ions in it will become difficult, and the polarization of the battery will increase; if the powder compaction is too low, the compaction density of the pole piece will be too low. Although the wettability of the pole piece can be improved, it will cause the contact performance between the negative electrode particles and between the negative electrode particles and the current collector to deteriorate, and the electronic conductivity of the negative electrode will be reduced. Therefore, the negative electrode material has a suitable powder compaction, which means that the negative electrode sheet has a suitable compaction density.
[0033] In addition, the powder compaction of the negative electrode material is related to the mechanical strength of the powder itself. The greater the mechanical strength, the higher the hardness of the powder particles, and the less likely it is to be compacted. Therefore, the powder compaction P of the negative electrode material is negatively correlated with the Young's modulus E of the material, that is, the larger the Young's modulus E, the smaller the powder compaction P; the smaller the Young's modulus E, the larger the powder compaction P. Affected by the Young's modulus E, the powder compaction P of the negative electrode material of the present invention at 80Mpa is 1.66≤P≤1.74g / cm 3 , which can maintain the high energy density of natural graphite while ensuring a high porosity between the electrode layers, thus having excellent fast charging performance. In some embodiments, the powder compaction P of the negative electrode material at 80 MPa can be 1.66 g / cm 3 , 1.70g / cm 3 or 1.74 g / cm 3 wait.
[0034] In one embodiment, after the negative electrode material is cold pressed at 160 MPa for 10 seconds, the micropore volume V of the pores with a pore size of 0.2 to 2 nm is 0.2-2 =14≤V 0.2-2 ≤20cm 3 / Kg. That is, the total volume of micropores with a pore size of 0.2 to 2 nm is 14-20 cm 3 / Kg. Specifically, it can be 14cm 3 / Kg、16cm 3 / Kg、18cm 3 / Kg or 20cm 3 / Kg, etc. The micropore volume has a significant effect on the electrochemical properties of the negative electrode material. The micropores can provide more active sites, increase the specific surface area of the material, and thus improve the kinetics of the electrochemical reaction; and the presence of micropores is conducive to the infiltration of the electrolyte and the diffusion of ions, which is crucial for the fast charging performance and cycle stability of the battery. However, if the micropore volume is too large, it will lead to an increase in side reactions, and if the micropore volume is too small, the kinetics of the electrochemical reaction of the negative electrode material will be poor. The negative electrode material of the present invention is cold pressed at 160Mpa for 10s, and the micropore volume reaches 14 to 20cm 3 / Kg means that the negative electrode material has abundant pores and can provide more fast lithium insertion channels, thus ensuring high energy density and good fast charging performance.
[0035] In addition, the negative electrode material still maintains a good pore structure under a high pressure of 160Mpa, thanks to the improvement of the mechanical properties of the negative electrode material itself. The Young's modulus of the negative electrode material of the present application is greatly improved compared to the existing natural graphite, which means that the particle hardness of the negative electrode material has been significantly improved. The material particle hardness is improved, and it is not easy to be squeezed, deformed or even broken under external force, so that the negative electrode material can still maintain a rich pore structure under high pressure.
[0036] In one embodiment, the coating layer is amorphous carbon. The surface of natural graphite has abundant functional groups. Amorphous carbon coated on the surface of natural graphite can avoid direct contact between natural graphite and electrolyte and reduce side reactions. In addition, the coating of amorphous carbon can also restrain the expansion of natural graphite and further improve its expansion problem. Amorphous carbon can be, for example, hard carbon or soft carbon. Furthermore, the mass of amorphous carbon accounts for 2.5% to 6% of the mass of natural graphite, which can be specifically listed as 2.5%, 4% or 6%.
[0037] In one embodiment, the particle size Dv50 of the negative electrode material is 5 μm to 20 μm. Dv50 represents the particle size corresponding to when the cumulative volume distribution reaches 50% in the particle size distribution. For example, the particle size Dv50 of the negative electrode material can be listed as 5 μm, 10 μm, 15 μm or 20 μm, etc.
[0038] The second aspect of the present invention provides a method for preparing a negative electrode material. The negative electrode material prepared by the preparation method can have a higher Young's modulus, so that the negative electrode material has the characteristics of low expansion and long cycle while maintaining the dynamics of natural graphite.
[0039] See also Figure 1 The method for preparing the negative electrode material comprises at least the following steps:
[0040] S1. crushing and shaping natural flake graphite raw materials to obtain a graphite precursor;
[0041] S2, performing a thermal shaping treatment on the graphite precursor, and then performing a cold quenching treatment on the graphite precursor by a gradient cooling method to obtain a spherical precursor;
[0042] S3, vacuum calcining the spheroidized precursor, and then forming a coating layer on the surface of the spheroidized precursor to obtain a negative electrode material.
[0043] Specifically, step S1 uses natural flake graphite as raw material, and pre-treats it before crushing and shaping it to remove impurity minerals in the raw material. The pre-treatment includes water washing and flotation. First, the natural flake graphite is washed with water to remove dirt, dust and other impurities on the surface of the graphite, in preparation for the subsequent flotation process. Flotation adds flotation agents to make the selective attachment of graphite particles and other impurity minerals on the water surface different, thereby separating graphite from other minerals and improving the purity of natural flake graphite.
[0044] Since the particle size of natural flake graphite is relatively large, which can reach the micron or even millimeter level, the natural flake graphite needs to be crushed and shaped after pretreatment to obtain a graphite precursor with a suitable particle size distribution. Specifically, it includes: high-frequency shaping of the natural flake graphite after water washing and flotation, so that the millimeter-level natural flake graphite size Dv50 is reduced to 30-50μm, and the larger and smaller sizes are removed by graded manner, so that the particle size distribution width (Dv90-Dv10) / Dv50 is less than 1.1. The above-mentioned high-frequency shaping can adopt conventional shaping methods in the art, such as using a honeycomb mill to shape the natural flake graphite at a high frequency of 90Hz for 6 hours. The honeycomb mill can effectively disperse and depolymerize the aggregated graphite flakes, reduce the damage to large flake graphite, and improve the quality of graphite products. It should be noted that Dv90 represents the particle size corresponding to 90% of the cumulative volume distribution in the particle size distribution; Dv10 represents the particle size corresponding to 10% of the cumulative volume distribution in the particle size distribution. The particle size distribution width (Dv90-Dv10) / Dv50 is an indicator to measure the uniformity of particle size. The larger the particle size distribution width, the wider the particle size distribution, that is, the greater the difference between large particles and small particles; the closer the particle size distribution width is to 0, the more uniform the particle size and the higher the size consistency. Step S1 reduces the particle size Dv50 of natural flake graphite to 30-50μm, and the particle size distribution width (Dv90-Dv10) / Dv50<1.1 can make the final negative electrode material meet its use particle size. Exemplarily, the Dv50 of the graphite precursor can be 30μm, 40μm or 50μm, etc.; the particle size distribution width (Dv90-Dv10) / Dv50 can be 1, 0.5 or 0, etc.
[0045] Step S2 first performs a thermal shaping treatment on the graphite precursor obtained in step S1, specifically including: collecting the graphite precursor obtained in step S1 and transferring it into a jet mill and heating it to a first temperature, and performing ultra-high frequency thermal shaping to improve its sphericity and compensate for the compaction of the material powder. The first temperature of the thermal shaping is 600°C to 800°C, for example, 600°C, 700°C or 800°C, etc. If the thermal shaping temperature is too high, it will increase its graphitization degree and destroy the original properties of natural graphite; and if the thermal shaping temperature is too low, it will lead to insufficient heat, and the target mechanical properties will not be achieved during the subsequent cold quenching process. Exemplarily, the frequency of thermal shaping is 100Hz to 140Hz, for example, 100Hz, 120Hz or 140Hz, etc., and the time of thermal shaping is 0.5h to 2h, for example, 0.5h, 1h, 1.5h or 2h, etc.
[0046] After the thermal shaping is completed, the graphite precursor is subjected to cold quenching treatment to obtain higher mechanical properties. Cold quenching treatment is to use an inert gas to perform gradient cooling on the precursor after thermal shaping. The above-mentioned inert gas can be nitrogen, helium, argon, etc. Gradient cooling means cooling to a certain temperature and keeping it for a period of time; then cooling to another temperature and keeping it for a period of time, and so on, until the set temperature is reached. The temperature difference of each cold quenching treatment should not be too large. If the temperature difference is too large, microcracks are easily generated inside the graphite. The temperature difference of the cold quenching treatment in the present invention is 100-400°C, specifically 100°C, 200°C, 300°C or 400°C, etc. The number of cold quenching treatments is at least once, preferably twice. If the number of times is too many, the improvement is not large, but it will cause energy consumption.
[0047] In one embodiment, the cold quenching treatment specifically includes: after the ultra-high frequency heat shaping is completed, introducing a first inert gas into the air flow mill to cool it down to a second temperature, and maintaining ventilation at the second temperature for 1 hour to 3 hours while shaping;
[0048] Then, a second inert gas is introduced into the air flow mill to cool the temperature to a third temperature, and the gas flow is maintained for 1 to 3 hours while shaping the product to obtain a spherical precursor.
[0049] Among them, the temperature difference between the second temperature and the heat shaping temperature (first temperature) is 100°C to 400°C, and the temperature difference between the second temperature and the third temperature is 100°C to 400°C. For example, the first temperature is 800°C, the second temperature is 400°C; the third temperature is 200°C; for another example, the first temperature is 600°C, the second temperature is 400°C, the third temperature is 200°C, and so on. After each cold quenching treatment, keeping warm for 1 to 3 hours can stabilize the crystal structure and keep it in a fixed microstructure. The holding time can be 1h, 2h or 3h, etc., which can be selected according to actual production.
[0050] The flow rate of the inert gas will affect the cooling rate. Therefore, the flow rate of the inert gas needs to be set within an appropriate range. Since the initial temperature during the first cooling is high, the cooling rate is not easy to be too large. Therefore, the flow rate of the first inert gas is relatively small; and the second cooling is based on the first cooling, and its initial temperature is relatively lower. Therefore, the flow rate of the inert gas can be appropriately increased during the second cooling. In some embodiments, the flow rate L1 of the first inert gas is 5L / min to 10L / min. For example, the flow rate L1 of the first inert gas can be 5L / min, 8L / min or 10L / min, etc.; the flow rate L2 of the second inert gas is 30L / min to 60L / min. For example, the flow rate L2 of the second inert gas can be 30L / min, 40L / min, 50L / min or 60L / min, etc. The first inert gas and the second inert gas are independently selected from nitrogen, argon or helium, that is, the first inert gas and the second inert gas can be the same or different. Preferably, the first inert gas and the second inert gas are the same, which can reduce production operations and simplify the operation process.
[0051] Step S3 is to calcine the spheroidized precursor obtained in step S2 under vacuum to remove the crystal water and organic groups in the material. The temperature of vacuum calcination is 450°C to 550°C, and can be 450°C, 500°C or 550°C, etc. The calcination time can be selected according to the actual production situation, for example, 1 to 3 hours. After the calcination is completed, it is cooled to room temperature, and then a coating layer is formed on the precursor after calcination to obtain a negative electrode material. The negative electrode material includes natural graphite and a coating layer. The negative electrode material prepared by the above preparation method has a high Young's modulus, suitable powder compaction and micropore volume, and has the characteristics of low expansion and long cycle while maintaining the dynamics of natural graphite, which improves the expansion problem of natural graphite as a negative electrode.
[0052] In one embodiment, the coating layer formed on the precursor is amorphous carbon, and the coating process of amorphous carbon is as follows: the vacuum calcined material is transferred to a solution containing a carbon-containing precursor, and the powder is collected after stirring, filtering and drying; then the powder is calcined at 750°C to 1100°C under an inert atmosphere for 4 to 8 hours to obtain a negative electrode material, and the negative electrode material is coated with a layer of amorphous carbon on the surface of natural graphite. The coating of amorphous carbon can avoid direct contact between natural graphite and electrolyte and reduce side reactions. In addition, amorphous carbon can also restrain the expansion of natural graphite, further improving the expansion problem of natural graphite.
[0053] The carbon-containing precursor in this step is the carbon source of amorphous carbon, including but not limited to one or more of C9 (main chain carbon atoms are 9) petroleum resin, phenolic resin, and asphalt. Furthermore, the carbon-containing precursor is C9 petroleum resin, and the molecular weight of C9 petroleum resin is small, which can make the coating of amorphous carbon more uniform. The specific steps are: the product powder after the roasting is transferred to a toluene solution dissolved with C9 petroleum resin through a pipeline. The mass fraction of C9 petroleum resin in the toluene solution is not limited and can be set according to its coating amount. Then, after stirring for a period of time, the powder is filtered and dried and collected. There is no restriction on the stirring and drying methods here. Any method and drying method that can disperse and mix materials in the art can be used, such as magnetic stirring, vacuum drying oven drying, etc. The collected powder is then calcined and carbonized in an inert gas atmosphere to obtain amorphous carbon-coated natural graphite. The calcination temperature is 750°C to 1100°C, such as 750°C, 900°C, 1000°C or 1100°C, and the calcination time is 4 to 8h, such as 4h, 6h or 8h.
[0054] After the above steps, the particle size Dv50 of the negative electrode material obtained is 5 μm to 20 μm.
[0055] The third aspect of the present invention provides a lithium ion battery, which includes a non-aqueous electrolyte lithium battery, a solid lithium battery, etc. Taking a non-aqueous electrolyte lithium battery as an example, the lithium ion battery includes a negative electrode sheet, a positive electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet includes the above-mentioned negative electrode material of the present invention or the negative electrode material prepared by the above-mentioned preparation method.
[0056] Specifically, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on the surface of at least one side of the negative electrode current collector. The negative electrode current collector may be made of conventional materials in the art, such as copper foil, carbon-coated copper foil, etc. The negative electrode active material layer may be disposed on the surface of one side of the negative electrode current collector, or on the surface of both sides. The negative electrode active material layer includes a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder, wherein the negative electrode active material is selected from materials capable of embedding and de-embedding lithium ions. In the present invention, the negative electrode active material is the above-mentioned negative electrode material. In other embodiments, it may also be a combination of the above-mentioned negative electrode material and other materials, such as a silicon-based negative electrode material, and the silicon-based negative electrode material includes a silicon oxide compound SiO x(0 < x < 2), silicon-carbon materials, silicon单质, etc. However, this application is not limited to the materials listed above, and other conventional materials that can be used as the negative electrode active material can also be used. These negative electrode active materials can be used alone or in combination of two or more. The negative electrode conductive agent can improve the electronic conductivity and play a role in collecting microcurrents between the negative electrode active materials and between the negative electrode active material and the negative electrode current collector, so as to reduce the contact resistance of the battery and accelerate the electron movement rate. In some embodiments, the negative electrode conductive agent includes at least one of conductive carbon black (SP), conductive graphite, carbon fiber, carbon nanotube, graphene. Optionally, the negative electrode conductive agent is conductive carbon black; or, a composition of carbon fiber and conductive carbon black; or, a composition of carbon nanotube and graphene, etc. The binder is used to bond the negative electrode active material and the negative electrode conductive agent and provide a certain adhesive force for the negative electrode active material layer to bond it to the negative electrode current collector. As an example, the negative electrode binder is selected from at least one of polyacrylic acid (PAA), polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), styrene-acrylate, acrylic acid-based multi-component copolymer. For example, the negative electrode binder is polyvinylidene fluoride, or a composition of styrene-butadiene rubber and carboxymethyl cellulose, etc. The proportions of the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder can refer to the conventional settings in the art.
[0057] An example of the preparation process of the negative electrode plate is as follows: First, the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder are mixed and stirred evenly in a solvent such as deionized water according to a certain ratio to form a negative electrode slurry, and then the negative electrode slurry is coated on the negative electrode current collector. After processes such as drying, rolling, and cutting, the negative electrode plate is obtained.
[0058] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector. The positive electrode current collector may be made of conventional materials in the art, such as aluminum foil, carbon-coated aluminum foil, etc. The positive electrode active material layer may be disposed on the surface of one side of the positive electrode current collector, or on the surface of both sides. The positive electrode active material layer includes a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder, wherein the positive electrode active material may be selected from any positive electrode material suitable for lithium-ion batteries, that is, compounds that can reversibly embed and deintercalate lithium ions may be used. As an example, the positive electrode active material may be a ternary material, such as a nickel-cobalt-manganese ternary material (NCM), a nickel-cobalt-aluminum ternary material (NCA), etc., and the iron-lithium positive electrode material may be, for example, lithium iron phosphate (LFP), lithium iron manganese phosphate (LMFP), etc., and may also be a traditional material such as lithium cobalt oxide, lithium manganese oxide, etc. These materials may be used alone or in combination. The positive electrode binder is, for example, any one or more of polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinyl ether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene or styrene-butadiene rubber (SBR), etc. The positive electrode conductive agent includes, but is not limited to, at least one of conductive carbon black (SP), conductive graphite, carbon fiber, carbon nanotubes, and graphene. Optionally, the conductive agent is conductive carbon black; or, a combination of carbon fiber and conductive carbon black; or, a combination of carbon nanotubes and graphene, etc. The ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder can refer to the conventional settings in the art.
[0059] The preparation process of the positive electrode sheet is exemplified as follows: first, the positive electrode active material, the positive electrode conductor and the positive electrode binder are mixed and stirred in a solvent such as N-methylpyrrolidone (NMP) in a certain ratio to form a positive electrode slurry, and then the positive electrode slurry is coated on the positive electrode collector. After drying, rolling, cutting and other processes, the positive electrode sheet is obtained.
[0060] The diaphragm is set between the positive electrode and the negative electrode to separate the positive electrode and the negative electrode to prevent short circuit inside the battery, and at the same time allow lithium ions to pass through and move between the positive and negative electrodes to realize the battery's charge and discharge process. The diaphragm can be made of porous materials such as polyethylene film (PE), polypropylene film (PP), glass fiber film or composite film. The thickness of the diaphragm is 9 to 18μm, the air permeability is 180s / 100mL to 380s / 100mL; the porosity is 30% to 50%.
[0061] The lithium-ion battery also includes an electrolyte, which plays a role in conducting lithium ions during the battery charge and discharge process. The electrolyte includes an organic solvent and a lithium salt, and the lithium salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalate phosphate) (LiDFOP) and lithium tetrafluorooxalate phosphate (LiTFOP). Further, the lithium salt is selected from lithium hexafluorophosphate with better comprehensive performance or a combination of lithium hexafluorophosphate and other lithium salts, such as a combination of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. The organic solvent may be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), and ethyl propyl carbonate (EPC). The electrolyte may also include functional additives such as fluoroethylene carbonate (FEC), propenyl-1,3-sultone (PST), tetravinylsilane (TVSI), vinylene carbonate (VC), and diethylene sulfate (DTD), which may be added according to actual production needs.
[0062] Battery assembly: Place the prepared positive electrode sheet, separator, and negative electrode sheet in sequence, with the separator placed between the positive and negative electrode sheets to isolate them, and obtain a bare cell by winding or stacking. Put the bare cell into the battery shell, and obtain a lithium-ion battery after assembly, injection, formation, and capacity division.
[0063] In other embodiments, the lithium-ion battery may also be a solid-state lithium-ion battery. The electrolyte of the solid-state lithium-ion battery is solid. Common solid-state electrolytes are oxide solid electrolytes, halide solid electrolytes, sulfide solid electrolytes, etc., which are not elaborated here. Those skilled in the art can make a selection according to actual production needs.
[0064] It should be noted that the structures not described in detail in the above lithium-ion battery can be configured with reference to the prior art and will not be described in detail here.
[0065] The lithium-ion battery of the present invention can be used in the form of a single cell, a battery module or a battery pack for electronic devices to power them. Electronic devices include but are not limited to mobile phones, tablets, laptops, electric toys, battery cars, new energy vehicles, ships, spacecraft, etc. Among them, electric toys can include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys and electric airplane toys, etc., and spacecraft can include airplanes, rockets, space shuttles and spacecraft, etc. New energy vehicles can be pure electric vehicles, hybrid vehicles or extended-range vehicles, etc.
[0066] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.
[0067] Example 1
[0068] This embodiment provides a negative electrode material, which includes natural graphite and amorphous carbon, wherein the amorphous carbon is uniformly coated on the surface of the natural graphite, and the coating amount of the amorphous carbon accounts for 4% of the mass of the natural graphite. The Young's modulus E of the negative electrode material is 13GPa, and the powder compaction P is 1.7g / cm 3 , micropore volume V 0.2-2 16.7cm 3 / Kg; the particle size Dv50 of the negative electrode material is 12.1μm.
[0069] This embodiment also provides a method for preparing the above-mentioned negative electrode material, comprising the following steps:
[0070] Step 1: The natural flake graphite after water washing and flotation is subjected to 90Hz high-frequency shaping for 6 hours using a honeycomb mill to reduce the millimeter-level natural flake graphite size Dv50 to 30-50μm, and grade and remove larger and smaller sizes to make its particle size distribution width (Dv90-Dv10) / Dv50 less than 1.1;
[0071] Step 2: Collect the above powders and transfer them into a jet mill and heat them to T1: 600°C, perform 120Hz ultra-high frequency shaping for 1h, then introduce inert gas from the upper end of the jet mill to cool it down to T2: 400°C, the inert gas flow rate is L1: 10L / min, keep ventilation for 2h and shape at the same time; then introduce inert gas from the upper end of the jet mill to cool it down to T3: 200°C, the inert gas flow rate L2: 30L / min, keep ventilation for 2h and shape at the same time, then stop heating to obtain a spherical precursor;
[0072] Step 3: calcining the spherical precursor at 500°C for 1 hour in vacuum, cooling it to room temperature, transferring it into a toluene solution containing C9 petroleum resin (the mass fraction of C9 petroleum resin is 20%) through a pipeline, stirring it for 5 hours, and then filtering and drying the collected powder;
[0073] Step 4: calcining the above powder at 900° C. in an inert gas atmosphere for 6 h, and then cooling to room temperature to obtain amorphous carbon-coated spherical natural graphite with a particle size of 12.1 μm.
[0074] Referring to Table 1, the present invention further provides Examples 2 to 8 and Comparative Examples 1 to 7.
[0075] The difference between Example 2 and Example 1 is that the Young's modulus E of the negative electrode material is 17 GPa, and the powder compaction P is 1.66 g / cm 3 , micropore volume V 0.2-2 19.2cm 3 / Kg; the particle size Dv50 of the negative electrode material is 11.5μm.
[0076] The heat shaping temperature T1 in the preparation method is changed to 800°C.
[0077] The difference between Example 3 and Example 1 is that the Young's modulus E of the negative electrode material is 8 GPa, and the powder compaction P is 1.74 g / cm 3 , micropore volume V 0.2-2 14.5cm 3 / Kg; the particle size Dv50 of the negative electrode material is 13.2μm.
[0078] The first quenching temperature T2 in the preparation method was changed to 500°C.
[0079] The difference between Example 4 and Example 1 is that the Young's modulus E of the negative electrode material is 11 GPa, and the powder compaction P is 1.72 g / cm 3 , micropore volume V 0.2-2 15.6cm 3 / Kg; the particle size Dv50 of the negative electrode material is 12.7μm.
[0080] The inert gas flow rate L1 in the preparation method was changed to 5 L / min.
[0081] The difference between Example 5 and Example 1 is that the Young's modulus E of the negative electrode material is 16 GPa, and the powder compaction P is 1.68 g / cm 3 , micropore volume V 0.2-2 17.8cm 3 / Kg; the particle size Dv50 of the negative electrode material is 11.6μm.
[0082] The inert gas flow rate L2 in the preparation method was changed to 60 L / min.
[0083] The difference between Example 6 and Example 1 is that the Young's modulus E of the negative electrode material is 16 GPa, and the powder compaction P is 1.67 g / cm 3 , micropore volume V 0.2-2 11.4cm 3 / Kg; the particle size Dv50 of the negative electrode material is 11.4μm.
[0084] In the preparation method, the heat shaping temperature T1 is changed to 700°C, the inert gas flow rate L1 is changed to 8 L / min; L2 is changed to 40 L / min.
[0085] The difference between Example 7 and Example 1 is that the Young's modulus E of the negative electrode material is 8 GPa, and the powder compaction P is 1.77 g / cm 3 , micropore volume V 0.2-2 14cm 3 / Kg; the particle size Dv50 of the negative electrode material is 8.9μm, and the coating amount of amorphous carbon accounts for 2.5% of the mass of natural graphite.
[0086] The mass fraction of C9 petroleum resin in the toluene solution containing C9 petroleum resin in step 3 of the preparation method is 12.5%.
[0087] The difference between Example 8 and Example 1 is that the Young's modulus E of the negative electrode material is 17 GPa, and the powder compaction P is 1.67 g / cm 3 , micropore volume V 0.2-2 20cm 3 / Kg; the particle size Dv50 of the negative electrode material is 12.8μm, and the coating amount of amorphous carbon accounts for 6% of the mass of natural graphite.
[0088] In step 3 of the preparation method, the mass fraction of C9 petroleum resin in the toluene solution containing C9 petroleum resin is 30%.
[0089] The difference between Comparative Example 1 and Example 1 is that the Young's modulus E of the negative electrode material is 6 GPa, and the powder compaction P is 1.82 g / cm 3 , micropore volume V 0.2-2 15.6cm 3 / Kg; Dv50 is 14.3μm.
[0090] The preparation method does not involve a heat shaping step.
[0091] The difference between Comparative Example 2 and Example 1 is that the Young's modulus E of the negative electrode material is 5 GPa, and the powder compaction P is 1.85 g / cm 3 , micropore volume V 0.2-212.3cm 3 / Kg; Dv50 is 15.2μm.
[0092] The preparation method does not perform heat shaping and T2 temperature rising steps, but directly quenches at T3 temperature.
[0093] The difference between Comparative Example 3 and Example 1 is that the Young's modulus E of the negative electrode material is 20 GPa, and the powder compaction P is 1.60 g / cm 3 , micropore volume V 0.2-2 21.3cm 3 / Kg; Dv50 is 10.9μm.
[0094] In the preparation method, no heat preservation step is performed after quenching at temperature T2.
[0095] Comparative Example 4 uses commercially available natural graphite. The difference between it and Example 1 is that the Young's modulus E of the negative electrode material is 2 GPa, and the powder compaction P is 1.79 g / cm 3 , micropore volume V 0.2-2 10.1cm 3 / Kg; Dv50 is 11.2μm.
[0096] The difference between Comparative Example 5 and Example 1 is that the Young's modulus E of the negative electrode material is 22 GPa, and the powder compaction P is 1.63 g / cm 3 , micropore volume V 0.2-2 22.4cm 3 / Kg; Dv50 is 11.7μm.
[0097] The preparation method adopts one cold quenching treatment, that is, T2 is 200°C, and T3 cold quenching process is not performed.
[0098] The difference between Comparative Example 6 and Example 1 is that the Young's modulus E of the negative electrode material is 27 GPa, and the powder compaction P is 1.54 g / cm 3 , micropore volume V 0.2-2 32.7cm 3 / Kg; Dv50 is 10.6μm.
[0099] In the preparation method, the heat shaping temperature T1 is 1000°C and the cold quenching temperature T2 is 400°C.
[0100] The difference between Comparative Example 7 and Example 1 is that: no amorphous carbon is coated; the Young's modulus E of the negative electrode material is 6 GPa, and the powder compaction P is 1.82 g / cm 3 , micropore volume V 0.2-2 14cm 3 / Kg; the particle size Dv50 of the negative electrode material is 10.6μm.
[0101] In the preparation method, after the roasting in step S3 is completed, the preparation is completed by cooling to room temperature without mixing with a toluene solution containing C9 petroleum resin and calcining in step S4.
[0102] Table 1: Parameter characteristics and preparation method parameters of negative electrode materials of Examples 1-8 and Comparative Examples 1-7
[0103]
[0104]
[0105] In order to verify the performance of the negative electrode material of the present invention, the inventors applied the negative electrode materials of Examples 1-8 and Comparative Examples 1-7 in lithium ion batteries, and performed performance tests on each lithium ion battery. The composition and test method of the lithium ion battery are as follows. The test results are shown in Table 2.
[0106] The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet, the separator and the negative electrode sheet are wound to obtain a battery cell, which is then packaged in a packaging shell and injected with an electrolyte to obtain a soft-pack battery.
[0107] Among them, the preparation of the negative electrode sheet: the negative electrode material obtained in the embodiment or the comparative example, the conductive agent (SP), the binder (PAA and SBR, the mass ratio of the two is 1.3:0.5) and the thickener carboxymethyl cellulose (CMC) are mixed in a mass ratio of 97.2:0.5:1.8:0.5 (a total of 100 parts by mass), and 82 parts by mass of deionized water are added and mixed evenly to obtain a negative electrode slurry; then the negative electrode slurry is evenly coated on the copper foil; and then after drying, rolling, cutting and other processes, a negative electrode sheet is prepared.
[0108] Preparation of positive electrode sheet: The positive electrode active material NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2), PVDF and SP are mixed in a mass ratio of 97:1.8:1.2 (a total of 100 parts by mass), and 82 parts by mass of NMP are added to obtain a positive electrode slurry; the obtained positive electrode slurry is coated on at least one surface of an aluminum foil, dried, and rolled to obtain.
[0109] Diaphragm: It is a polyethylene film with a thickness of 11 μm; the air permeability of the diaphragm is 230 s / 100 mL; and the porosity of the diaphragm is 40%.
[0110] The electrolyte used was a commercial electrolyte (manufacturer: Xinya Shanshan New Materials Technology (Quzhou) Co., Ltd., model: E3).
[0111] Battery performance test method
[0112] (1) Full battery first effect
[0113] Full battery charging capacity: Charge the lithium-ion battery to 4.35V with a current of 1C, record the charging capacity at this stage as c1, and then charge at a constant voltage until the cut-off current is 0.05C. The charging capacity at this stage is c2, and the full battery charging capacity is the sum of c1 and c2.
[0114] Full battery discharge capacity: Fully charge the cell, rest for 30 minutes, then discharge to 2.8V with 1C current, and record the discharge capacity c3 at this stage, which is the full battery discharge capacity.
[0115] First effect = full battery discharge capacity c3 / full battery charge capacity (c1 + c2) × 100%.
[0116] (2) Fast charging time
[0117] Directly charge to 8% SOC state with 0.33C current, and then test the charging windows of 10%, 20%, 30%, 40%, 50%, 60%, 70%, and 80% according to the actual measurement of the three-electrode window of the battery cell, which are c1, c2, c3, c4, c5, c6, c7, and c8 respectively. Use stepcharge to charge to 80%, that is, 8%-10% with c1, 10% to 20% with c2, and so on. Record the charging time from 8% to 80% SOC state as the measure of fast charging capability. The calculation formula is:
[0118] T(8%-80%)=(0.02 / c1+0.1 / c2+0.1 / c3+0.1 / c4+0.1 / c5+0.1 / c6+0.1 / c7+0.1 / c8)*60.
[0119] (3)Number of cycles at room temperature
[0120] At 25°C, the material was cycled at 0.21A / g (calculated based on the mass of the positive electrode active material) and 2.8-4.25V. The number of cycles when the initial capacity reached 80% was recorded as the material cycle performance effect.
[0121] (4) Storage days
[0122] At 25°C, the capacity is fixed with a current of 0.33C and recorded as C0. The battery cells are then stored at a high temperature of 60°C. After that, the battery cells are taken out every 7 days and the capacity is tested at room temperature and recorded as C1, C2, ..., Cn, until Cn is less than or equal to 80% of C0 for the first time. The number of days is used as a measure of the storage capacity and is recorded as storage days.
[0123] Table 2: Performance of assembled batteries of Examples 1-8 and Comparative Examples 1-7
[0124]
[0125]
[0126] It can be seen from Tables 1 and 2 that the Young's modulus, powder compaction and micropore volume of the negative electrode material can be adjusted by adjusting the heat treatment parameters during the preparation process. The Young's modulus of the negative electrode materials obtained in Examples 1 to 8 has been significantly improved compared to the currently commercially available natural graphite (Comparative Example 4), and the cycle performance, fast charging performance and storage performance of the assembled battery at room temperature have been significantly improved compared to Comparative Example 4. This shows that the appropriate increase in the Young's modulus of the negative electrode material can maintain the microscopic crystal structure during lithium ion deintercalation and reduce irreversible deformation, thereby improving the cycle performance. At the same time, the Young's modulus of the negative electrode material is increased, and the powder compaction and micropore volume also change accordingly, so that it has better porosity and better electrolyte wettability, so as to have good fast charging performance.
[0127] The amount of amorphous carbon coating on the negative electrode material in Example 7 is relatively small compared with other examples, resulting in a relatively large volume expansion of the negative electrode material and poor stability, so the number of cycles is relatively small compared with other examples; the amount of amorphous carbon coating on the negative electrode material in Example 8 is relatively large compared with other examples, the powder compaction of the negative electrode material is poor, and the porosity (relative to other examples) is smaller under the same compaction density of the electrode sheet, and the wettability with the electrolyte is poor, so the number of cycles is also smaller.
[0128] The Young's modulus, powder compaction or micropore volume of the negative electrode materials of Comparative Examples 1-3 and Comparative Examples 5-6 exceed the range specified in this application, and the cycle performance, fast charging performance and storage performance of the assembled batteries are all poorer than those of Examples 1-8. The negative electrode material of Comparative Example 7 contains only natural graphite, and the surface of natural graphite is not coated with amorphous carbon. Since the surface activity of amorphous carbon is better than that of natural graphite, the surface of natural graphite is not coated with amorphous carbon. Compared with the case of coating amorphous carbon, the side reactions will be reduced, and the high temperature storage performance will be relatively better, but the fast charging performance and cycle performance will be worse.
[0129] The negative electrode material provided by the present invention has a high Young's modulus, so that the negative electrode material particles have a high mechanical strength, can better maintain the microscopic crystal structure when lithium ions are deintercalated, and undergo a smaller irreversible deformation, thereby having better cycle performance. In addition, due to the high Young's modulus of the negative electrode material, the powder compaction of the material is maintained within an appropriate range, while having a high energy density, ensuring a high porosity at the pole piece level, and having excellent fast charging performance; and the negative electrode material maintains a large amount of micropore volume under high pressure, so that it has more rapid lithium insertion channels, ensuring that the material has good fast charging performance under high energy density. Therefore, the present invention effectively overcomes some practical problems in the prior art and has a high utilization value and use significance.
[0130] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A negative electrode material, characterized in that: The Young's modulus E of the negative electrode material is 8GPa≤E≤17GPa; the negative electrode material includes natural graphite and a coating layer coated on the surface of the natural graphite.
2. The negative electrode material according to claim 1, characterized in that The value of the powder compaction P of the negative electrode material at 80 MPa is 1.66≤P≤1.74 g / cm 3 .
3. The negative electrode material according to claim 1 or 2, characterized in that: After the negative electrode material is cold pressed at 160 MPa for 10 seconds, the micropore volume V of the pores with a pore size of 0.2 to 2 nm is 0.2-2 =14≤V 0.2-2 ≤20cm 3 / Kg.
4. The negative electrode material according to claim 1, characterized in that The coating layer includes amorphous carbon, and the mass of the amorphous carbon accounts for 2.5% to 6% of the mass of the natural graphite.
5. The negative electrode material according to claim 1, characterized in that The particle size Dv50 of the negative electrode material is 5 μm to 20 μm.
6. A method for preparing the negative electrode material according to claim 1, characterized in that: The following steps are involved: The natural flake graphite raw material is crushed and shaped to obtain a graphite precursor; Performing a thermal shaping treatment on the graphite precursor, and then performing a cold quenching treatment on the graphite precursor by a gradient cooling method to obtain a spherical precursor; The spheroidized precursor is vacuum calcined, and then a coating layer is formed on the surface of the spheroidized precursor to obtain a negative electrode material.
7. The method for preparing the negative electrode material according to claim 6, characterized in that: The step of performing a thermal shaping treatment on the graphite precursor and then performing a cold quenching treatment on the graphite precursor by a gradient cooling method comprises: The graphite precursor is transferred into a jet mill and heated to a first temperature, and subjected to ultra-high frequency heat shaping at 100 Hz to 140 Hz for 0.5 h to 2 h; Afterwards, a first inert gas is introduced into the jet mill to cool the temperature to a second temperature, and ventilation is maintained at the second temperature for 1 hour to 3 hours while shaping; Then, a second inert gas is introduced into the jet mill to cool the temperature to a third temperature, and the gas is maintained for 1 to 3 hours while shaping the product to obtain a spherical precursor; Among them, the first temperature is 600℃ to 800℃; the temperature difference between the first temperature and the second temperature is 100℃ to 400℃, the temperature difference between the second temperature and the third temperature is 100℃ to 400℃, the flow rate L1 of the first inert gas is 5L / min to 10L / min; the flow rate L2 of the second inert gas is 30L / min to 60L / min.
8. The method for preparing the negative electrode material according to claim 6, characterized in that: The vacuum calcination temperature is 450°C to 550°C; The step of forming a coating layer on the surface of the spherical precursor comprises: transferring the vacuum calcined precursor to a solution containing a carbon-containing precursor, stirring, filtering and drying, and collecting powder; Then, the powder is calcined at 750° C. to 1100° C. for 4 to 8 hours under an inert atmosphere to obtain a negative electrode material; And / or, the particle size Dv50 of the graphite precursor is 30 μm to 50 μm, and the particle size distribution width (Dv90-Dv10) / Dv50 is less than 1.
1.
9. The method for preparing the negative electrode material according to claim 8, characterized in that: The carbon-containing precursor includes one or more of C9 petroleum resin, phenolic resin and asphalt.
10. A lithium ion battery, characterized in that: It comprises a negative electrode plate, wherein the negative electrode plate comprises the negative electrode material according to any one of claims 1 to 5 or the negative electrode material prepared by the preparation method according to any one of claims 6 to 9.